Cds Quantum Dots Composite Sol-gel Rod for Optical Applications - M. Naziruddin KHAN; Abdullah ALMOHAMMEDI (Medžiagotyra)
Colloidal quantum dots (QDs) based on CdS were directly incorporated into a sol to fabricate solid rods. Various characterization techniques were employed to study the properties of the composite rod. A comparison between the absorption, emission, and excitation spectra of the QDs in the solid rod and in solution revealed their significant and stable nature in the solid state. SEM image shows that QD particles are well interacted with the sol gel environment. The observed particle size of QDs was heteronomous approximately from 5 to 10 nm. The XRD pattern of QDs illustrates their crystalline nature. The significant spontaneous emission (SE) signal was enhanced from QDs composite rod under the excitation of a 355 nm Pico second laser source. These findings suggest that further improvements in the integration of QDs into sol gel rods could be achieved by employing a higher density of QDs in the solid rod. The fabrication of QDs composite rods with a high concentration holds the potential for testing stimulated or amplified spontaneous emission in future studies.